Soluble beta amyloid evokes alteration in brain norepinephrine levels: role of nitric oxide and interleukin-1 - Morgese, Maria G.; Colaianna, Marilena; Mhillaj, Emanuela; Zotti, Margherita; Schiavone, Stefania; D'Antonio, Palma; Harkin, Andrew; Gigliucci, Valentina; Campolongo, Patrizia; Trezza, Viviana; De Stradis, Angelo; Tucci, Paolo; et al. (Frontiers in Neuroscience, 2015)
Strong evidence showed neurotoxic properties of beta amyloid (Aβ) and its pivotal role in the Alzheimer’s disease (AD) pathogenesis. Beside, experimental data suggest that Aβ may have physiological roles considering that such soluble peptide is produced and secreted during normal cellular activity. There is now suggestive evidence that neurodegenerative conditions, like AD, involve nitric oxide (NO) in their pathogenesis. Nitric oxide also possess potent neuromodulatory actions in brain regions, such as prefrontal cortex (PFC), hippocampus (HIPP) and nucleus accumbens (NAC). In the present study, we evaluated the effect of acute Aβ injection on norepinephrine (NE) content before and after pharmacological manipulations of nitrergic system in above mentioned areas. Moreover, effects of the peptide on NOS activity were evaluated. Our data showed that 2 hours after i.c.v. soluble Aβ administration, NE concentrations were significantly increased in the considered areas along with increased iNOS activity. Pre-treatment with NOS inhibitors, 7-Nitroindazole (7-NI) and N6-(1-iminoethyl)-L-lysine-dihydrochloride (L-NIL), reversed Aβ-induced changes. Ultimately, pharmacological block of interleukin1 (IL-1) receptors prevented NE increase in all brain regions. Taken together our findings suggest that NO and IL-1 are critically involved in regional noradrenergic alterations induced by soluble Aβ injection.